Oxygen-permeable microwell device maintains islet mass and integrity during shipping. Issue 3 (March 2018) - Rojas-Canales, Darling M; Waibel, Michaela; Forget, Aurelien; Penko, Daniella; Nitschke, Jodie; Harding, Fran J; Delalat, Bahman; Blencowe, Anton; Loudovaris, Thomas; Grey, Shane T; Thomas, Helen E; Kay, Thomas W H; et al.
Abstract : Islet transplantation is currently the only minimally invasive therapy available for patients with type 1 diabetes that can lead to insulin independence; however, it is limited to only a small number of patients. Although clinical procedures have improved in the isolation and culture of islets, a large number of islets are still lost in the pre-transplant period, limiting the success of this treatment. Moreover, current practice includes islets being prepared at specialized centers, which are sometimes remote to the transplant location. Thus, a critical point of intervention to maintain the quality and quantity of isolated islets is during transportation between isolation centers and the transplanting hospitals, during which 20–40% of functional islets can be lost. The current study investigated the use of an oxygen-permeable PDMS microwell device for long-distance transportation of isolated islets. We demonstrate that the microwell device protected islets from aggregation during transport, maintaining viability and average islet size during shipping.